Chitosan mucoadhesive patch combination of rambutan (Nephelium lappaceum L) peel extract decrease leukocyte cell in gingivitis animal model - Widodorini , Trining; Safitri, Maheswari Nestivia (Indonesian Journal of Dental Medicine, 2025)
Background: Gingivitis, or inflammation of the gingiva, is characterized by increased leukocyte cells as a sign of an inflammatory response. A mucoadhesive patch made from chitosan combined with rambutan (Nephelium lappaceum L) peel extract can reduce inflammation in the gingiva. Chitosan has been proven to inhibit bacterial growth. Meanwhile, rambutan peel extract, as an active ingredient, acts as an anti-inflammatory and anti-bacteria. Purpose: This study aimed to examine the impact of administering rambutan (N. lappaceum L.) peel extract in chitosan mucoadhesive patches made from blood clam shell waste as a treatment for gingivitis on the total leukocyte cell count in white rats. Methods: This research used a true-experimental, post-test-only randomized control group design study, an in vivo study. Wistar rat (Rattus novergicus) gingiva was induced with lipopolysaccharide (LPS) Porphyromonas gingivalis (Pg) for two  days and then treated with a mucoadhesive patch for six consecutive days. Histological preparations were made with hematoxylin eosin (HE) staining using a light microscope to observe the total number of leukocyte cells in Wistar rat (R. novergicus) gingival tissue. Results: Based on the outcomes of this study, the Kruskal-Wallis statistical test obtained the total number of leukocyte cells, showing a significant decrease (p < 0.05) at the active ingredient concentrations of 10% and 15% rambutan (N. Lappaceum L.) peel extract in chitosan mucoadhesive patches against the positive control group. Conclusion: Rambutan (N. lappaceum L.) peel extract in chitosan mucoadhesive patches was able to reduce total leukocyte cell count in gingivitis of Wistar rats (Rattus novergicus).